The study on payment zakat business to Lembaga Zakat Negeri Kedah among muslim enterpreneurs in Kedah - Muhammad Nasrul, Ridzuan (2021)
This study aims to examine the payment of business zakat among Muslim entrepreneurs in the state of Kedah. For the purpose of this research is to identify the trend of business zakat collection, the role of the Lembaga Zakat Negeri Kedah in encouraging Muslim entrepreneurs to pay zakat and the practice of business zakat payment by Muslim entrepreneurs in the state of Kedah.Therefore, to ensure that all the objectives that have been listed are answered gradually, the most appropriate method that can be used is a qualitative research methodology. This research combines literature sources and interview methods. The results of the study found that the trend of business zakat collection starting in 2013 until 2019 is uncertain, most Muslim entrepreneurs choose to pay to the Kedah State Zakat Board because it is easy and confident in the distribution made by the Kedah State Zakat Board. The researcher also suggested some improvements to the LZNK zakat institution to overcome the problems that occurred. In conclusion, the LZNK zakat institution must take several actions to ensure that business zakat collection can be increased.